1997
DOI: 10.1002/pen.11836
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial orientation of poly(vinyl chloride) compounds: Interaction between drawing, structure, and properties

Abstract: Rigid poly(viny1 chloride) (PVC) sheets were stretched uniaxially (at constant width), equally biaxially, and unequally biaxially to various draw ratios. Tensile properties, density, and birefringence of the stretched sheets were measured, and their wide angle X-ray diffraction traces recorded. Comparison of results showed the highest crystallite and overall orientation and density in the uniaxial samples, and lowest values for the equal biaxial samples. Drawing resulted in the alignment of some existing cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The increased orientation observed here correlates with improved mechanical properties. 10 The 3D facility has enabled the second distribution to be investigated in more detail in uniaxially drawn films than previously, 11 and lead to a reinterpretation of this crystallite orientation. Guerrero 12 had also found that the second distribution of crystallites was present at a higher concentration in films drawn to a higher draw ratio, as is observed here.…”
Section: Discussionmentioning
confidence: 96%
“…The increased orientation observed here correlates with improved mechanical properties. 10 The 3D facility has enabled the second distribution to be investigated in more detail in uniaxially drawn films than previously, 11 and lead to a reinterpretation of this crystallite orientation. Guerrero 12 had also found that the second distribution of crystallites was present at a higher concentration in films drawn to a higher draw ratio, as is observed here.…”
Section: Discussionmentioning
confidence: 96%
“…From the studies at IPTME [5][6][7][8] on the effects of orientation on the properties of rigid PVC it has been found that both yield strength and tensile strength follow the same pattern when properties are plotted against planar strain. (This is essentially the product of the draw ratios applied to the material, for example, PVC sheets stretched uniaxially to draw ratios of 3.0 x 1.0 and equally biaxially to 1.73 x 1.73 have the same planar strain of 3.0.)…”
Section: The Dependence Of Mechanical Strength Of Oriented Rigid Pvc mentioning
confidence: 99%
“…in which p is a hydrostatic pressure, I is the identity tensor, and f σ is the filament stress given by (6).…”
Section: Application Of the Filament Theory To Predict Yield Stress Imentioning
confidence: 99%
See 2 more Smart Citations